(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides information about post-infectious obliterative bronchiolitis, including its etiology, pathogenesis, clinical features, diagnostics, treatment, and preventive methods. Post-infectious obliterative bronchiolitis is a rare condition that develops following an infectious process in the respiratory tract and is characterized by inflammation and obliteration of the terminal bronchioles, clinically manifesting as progressive respiratory failure. It is demonstrated that early diagnosis and comprehensive treatment of the disease can improve the patient’s quality of life.